Compliance e integridade no Ministério da Saúde e a aplicação da metateoria do direito fraterno na resolução dos conflitos sanitários - Lucena, Victor Felipe Fernandes de (2024)
The management of public policies on the right to health is analyzed within the scope of the Brazilian Ministry of Health, which has a central and articulating role with states and municipalities, as well as the effectiveness of investments in the health sector, researching transparency and the integrity of national health policy. In this context, compliance and integrity, originating from the private sector, emerge as tools capable of strengthening the management of public health law policies, providing greater efficiency and quality in the services provided to the population. In this aspect, the problem faced in the research refers to the operationalization of compliance and integrity mechanisms in the corporate governance of the public health sector, in line with ethical standards of conduct and the internal and external controls of public institutions, in order to guarantee that resources are used appropriately and that decisions are made ethically and impartially. The research analyzes mechanisms for preventing and combating corruption in the public policy sector regarding the right to health, with the incidence of anti-corruption legislation, aiming to optimize the use of resources and avoid waste, favoring a democratic and participatory environment for all competent institutions. To resolve the problem, sharing decision-making power. In this context, it is proposed to apply the metatheory of fraternal law, in the concept developed by Eligio Resta, which has potential for resolving health conflicts, also as a form of dejudicialization of the right to health, through the resumption of dialogue, representativeness and the participation of civil society, with special action from the National Health Council. It is also proposed to use mediation techniques in any disputes that may arise, raising awareness and engaging all those involved in the management of public policies, favoring an extrajudicial macro-solution of the fundamental right to health in Brazil. It is concluded that the importance of using compliance monitoring tools, as a way of monitoring and implementing the strategic plan resulting from institutional dialogue, being an innovation that allows greater transparency in the application of public resources, as well as the achievement of social justice in the administrative scope, in order to achieve the dejudicialization of the right to health and achieve a certain social pacification, with the fulfillment of health demands presented to the Public Power and the achievement of quality health for all, seeing others as equal and favoring the good -being collective. The methodology used in this thesis covers the development of bibliographical research, in physical and/or virtual media, in books and doctrinal articles, with historical-legal and legal-exploratory research, in addition to the analysis of the relevant legislation and jurisprudential sources on the matter.